O Fantástico Mistério de Feiurinha, de Pedro Bandeira e Reinações de Narizinho, de Monteiro Lobato: diálogos intertextuais com os contos de fadas - Sarro, Elenir (2009)
This work analises the writings Reinações de Narizinho, particularly, the excerpt Cara de Coruja , by Monteiro Lobato and O Fantástico Mistério de Feiurinha by Pedro Bandeira recovering the fairy tales. Visiting the classic narratives, the intertextual dialogue is established between the oral tradition and modern and contemporary texts based in building procedures that bring to evidence the humor and the parody. The adopted methodology used for reading the corpus is descriptive-analytical. The theoretical support that backgrounds the identification of the intertextuality and parody in the selected writings are referred in the authors Mikhail Bakhtin, Julia Kristeva, Linda Hutcheon e Affonso Romano de Sant Anna. In the study of fairy tales André Jolles e Nelly Novaes Coelho deserve to be emphasized. Monteiro Lobato innovates children s literature inserting criticism and freedom of expression, disrupting the traditional pattern. In the specific case of the recovery of fairy tales, Monteiro Lobato institutes the dialogical scene, modifying the narrator s status now less authoritative and closer to the reader. Through intertextuality, the author revisits the traditional narratives, creating a new way of telling these stories giving bigger dynamicity to the text, due to the colloquialism adopted in the language, in addition to the active participation of several characters, specially the childish ones. Pedro Bandeira takes the same direction intensifying the parodistic effect building the narrative, what leads to the supposition of his affiliation to Monteiro Lobato when you verifies that to build the dialogue with oral tradition in O Fantástico Mistério de Feiurinha, firstly, the author revisits the episodes of Reinações de Narizinho